Attitudes and Perceptions of Telemedicine in Response to the COVID-19 Pandemic: A Survey of Naïve Healthcare Providers - Schinasi, Dana A.; Foster, Carolyn C.; Bohling, M. Katie; Barrera, Leonardo; Macy, Michelle L. (Frontiers in Pediatrics, 2021)
Introduction: Expansion of telemedicine enabled healthcare access during the COVID-19 pandemic. In response to in-person visit restrictions, our institution trained >1,000 clinicians in telemedicine. Little is known about telemedicine-naïve pediatric healthcare provider’s perceptions as they adopted telemedicine practice. Methods: We conducted a cross-sectional survey of clinicians after expanding telemedicine practice at an independent children’s hospital. The survey assessed experience with, concerns about, and intentions to continue telemedicine. Outpatient providers were included if they were first trained for telemedicine in response to COVID-19 and conducted at least one video visit, 3/21/2020-6/30/2020. Descriptive statistics were calculated; perceptions were compared across telemedicine activity level quartiles (based on proportions of visits delivered by video in June 2020) using Fisher’s exact tests. Results: Of 609 survey responses, 305 (50.1%) met inclusion criteria, representing various roles and disciplines. Over half (54.1%) conducted >20 video visits 3/21/2020-6/30/2020. More than 75% of providers found telemedicine easy to learn. Providers with greater proportions of video visits in a typical week in June reported greater ease of incorporating telemedicine into clinical practice and greater intention to continue telemedicine practice in 6 months. Nearly all providers endorsed concerns. Patient care experiences reinforced technology-related concerns and alleviated liability and privacy concerns. Payer reimbursement was the leading influencer of anticipated future use of telemedicine. Discussion: Providers who conducted more telemedicine encounters reported greater ease of incorporating telemedicine into practice. Provider concerns were influenced by patient care experiences. Targeted training and quality improvement strategies are needed to sustain a robust post-pandemic telemedicine program.